The effect of soil burrowing earthworm Pontoscolex corethrurus on chili (Capsicum annum cv. Kulai) production - Kok, Ho Yin; Abdul Aziz, Nor Azwady; Loh, Khye Er; Mustafa, Muskhazli; Zulkifli, Syaizwan Zahmir (2012)
A field experiment was conducted to evaluate the effect of soil burrowing earthworm Pontoscolex corethrurus on chili (Capsicum annum cv. Kulai) production. Chilies were grown in a standard growth medium and two treatments were defined: earthworm free medium (control) and earthworm inoculated medium. Although there was no significant different on the number of chilies produced by plant in earthworm inoculated medium and their counterpart with no earthworm inoculation, the fresh weight of chili produced by the former was significantly different. The yield of chilies in medium with earthworm inoculated (112.59 ± 2.34g) was significantly higher than the earthworm free medium (100.95 ± 2.00g). This study suggested that inoculation of Pontoscolex corethrurus has beneficial impact on yield of chili in the field.